2021
DOI: 10.1111/opo.12878
|View full text |Cite
|
Sign up to set email alerts
|

The impact of spectacle lenses for myopia control on visual functions

Abstract: Purpose Spectacle lenses containing multiple small peripheral elements have been developed for myopia control in children. It is important that their effect on vision be quantified by (i) fixation through the peripheral portion, thereby using foveal vision and (ii) by fixation through the central portion and presentation of peripheral targets. Methods The above approaches were used in five studies to evaluate two novel spectacle lens designs: spectacle lenses with Highly Aspherical Lenslets (HAL) and Slightly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 54 publications
(107 reference statements)
3
57
1
Order By: Relevance
“…In previous studies (Gao et al, 2021;Li et al, 2021), the HAL lens was found to have only a small impact on visual acuity. When looking directly through the lenslets, high contrast VA was reduced by HAL for 0.07 logMAR, which is only slightly more than half a line, in children (Li et al, 2021); for adults (Gao et al, 2021), high contrast VA was also reduced by 0.07 logMAR and low contrast VA was reduced by 0.14 logMAR. Another myopia control spectacle lens with a honeycomb configuration of spherical lenslets (HC) was found to reduce VA for about one line (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In previous studies (Gao et al, 2021;Li et al, 2021), the HAL lens was found to have only a small impact on visual acuity. When looking directly through the lenslets, high contrast VA was reduced by HAL for 0.07 logMAR, which is only slightly more than half a line, in children (Li et al, 2021); for adults (Gao et al, 2021), high contrast VA was also reduced by 0.07 logMAR and low contrast VA was reduced by 0.14 logMAR. Another myopia control spectacle lens with a honeycomb configuration of spherical lenslets (HC) was found to reduce VA for about one line (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 79%
“…HC was found to influence CS to a larger degree in various conditions (Li et al, 2021). The study conducted on adults (Gao et al, 2021) found that HAL had no significant impact on peripheral visual functions including useful field of view (UFOV), peripheral motion detection, and peripheral coherent motion direction discrimination.…”
Section: Introductionmentioning
confidence: 94%
“…When the subjects first used the HAL and SAL at baseline, it could be that the participants did not fixate completely through the center of the lens (without lenslets area) but partly through the central area and partly through the peripheral aspherical lenslets area. A previous study found that low-contrast scotopic VA was reduced when fixating through the lenslets area of HAL and SAL [ 23 ]. Therefore, during the 1-year wearing period, children learned to use the lenses (find the clear center area), the influence of aspherical lenslets was reduced, and the VA improved significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The 1-year results showed 0.11 mm and 0.33 D decreases in axial length (AL) elongation and spherical equivalent refraction (SER) progression in the spectacle lenses with slightly aspherical lenslets (SAL) group compared with the SVL group and 0.23 mm and 0.53 D decreases in AL and SER progression in the spectacle lenses with highly aspherical lenslets (HAL) group compared with the SVL group [ 21 ]. Two studies have shown that HAL and SAL have low impact on short-term visual acuity and contrast sensitivity in children and adult population [ 23 , 24 ]. However, the long-term impacts on various aspects of visual function and visual quality of HAL and SAL in myopic children are yet to be investigated, which is the aim of this study.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of this therapy shows a longer correction time. Therefore, this therapeutic option tends to be more recommended as an optical tool to slow the development and progression of myopia patients [37].…”
Section: Spectacles Lensmentioning
confidence: 99%